2009
DOI: 10.1007/s00468-009-0379-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycorrhizae on seedlings of six endemic Mimosa L. species (Leguminosae–Mimosoideae) from the semi-arid Tehuacán–Cuicatlán Valley, Mexico

Abstract: Mimosa is an important genus of legumes in arid and semi-arid ecosystems of the world, but scarce information is available about its interaction with microbial symbionts. In Mexico, there are no reports on the responsive of endemic Mimosa species to arbuscular mycorrhizal (AM) fungal colonization. In this study, the AM association with seedlings of six endemic Mimosa species, M. adenantheroides, M. calcicola, M. lacerata, M. luisana, M. polyantha and M. texana var. filipes, is reported. Field conditions were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
1
4
0
14
Order By: Relevance
“…AM fungi may be advantageous to desert plants, when P is practically insoluble, and its diffusion in the soil is further decreased by low soil moisture (Tarafdar & Panwar 2008). Furthermore, P availability under the canopy of both legumes may also be favored by a low soil Ca and Mg concentration, and a slightly acid pH, which agrees with a higher AM fungal spore abundance in the soil under the canopies of both legumes (Camargo-Ricalde et al 2010b). Smith & Read (2008) indicate that the plant-root colonization by AM fungi decreases when P availability is high in the soil, increasing AM fungal spore production.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…AM fungi may be advantageous to desert plants, when P is practically insoluble, and its diffusion in the soil is further decreased by low soil moisture (Tarafdar & Panwar 2008). Furthermore, P availability under the canopy of both legumes may also be favored by a low soil Ca and Mg concentration, and a slightly acid pH, which agrees with a higher AM fungal spore abundance in the soil under the canopies of both legumes (Camargo-Ricalde et al 2010b). Smith & Read (2008) indicate that the plant-root colonization by AM fungi decreases when P availability is high in the soil, increasing AM fungal spore production.…”
Section: Discussionsupporting
confidence: 57%
“…These species improve fertility and create resource islands, due to that modify of the micro-environmental conditions and function as reservoirs of soil nutrients, fungi spores and microorganisms under their canopies (Reynolds et al 1999, Camargo-Ricalde & Dhillion 2003, González-Ruiz et al 2008. For instance, arbuscular mycorrhizal fungi are critical to plant establishment, because they improve water and nutrients status of the host plant growing in arid regions (Tarafdar & Panwar 2008, Camargo-Ricalde et al 2010b. Even so, the effect of Prosopis and Mimosa species has been documented for each single species, without elucidating the interactions that could take place among them and with other plant species within the plant community.…”
mentioning
confidence: 99%
“…overwhelmingly prefer to nodulate with Burkholderia rather than Cupriavidus or Rhizobium , (Elliott et al ., ; Melkonian et al ., ), but the predominance of Burkholderia can be overcome at higher N concentrations, which demonstrates that soil N‐content is an important factor in Mimosa symbiont selection (Elliott et al ., ). Furthermore, soils in central Brazil are generally acid (many are less than pH 5.0; dos Reis Junior et al ., ), which would favour the acid‐tolerant genus Burkholderia (Garau et al ., ; Stopnisek et al ., ), whereas those from central Mexico are either weakly acidic, neutral or slightly alkaline (Camargo‐Ricalde et al ., ; this study), which would favour most species of Rhizobium , and also Cupriavidus (Klonowska et al ., ; Liu et al ., ; Mishra et al ., ; Gehlot et al ., ). Further studies using soils and seeds from both Brazil and Mexico could help to determine if (and what) soil characteristics are factors in the selection of symbionts by Mimosa spp.…”
Section: Discussionmentioning
confidence: 67%
“…However, interspecific differences were not observed in Nt, because Mimosa species may be N 2 -fixing species, which increases the N circulation in a similar way among species. Camargo-Ricalde et al (2010) reported from 4 to 25 N 2 -fixing nodules in all four species here studied. Nevertheless, Pi varied the most across species due to differences in P content in tissues or to the level of mycorrhizal association among species .…”
Section: Discussionmentioning
confidence: 95%